Perilaku Harian Burung Tekukur (Streptopelia Chinensis) Di Lapangan Tenis Universitas Lampung - Lulu Subangkit; Samsul Bakri; Susni Herwanti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
One of nature conservation area in Indonesia is a Way Kambas National Park (WKNP). Ecotourism activities in TNWK located in Elephant Conservation Center (ECC), which success is determined by the satisfaction of visitors. The purpose of the study was conducted in May-June 2013 were to (1) determine factors of visitor satisfaction (2) determine the strategy of increasing visitor satisfaction at the Elephant Conservation Centre Way Kambas National Park. Survey methods used to conduct interviews with 98 respondents. The data used (1) characteristics of the attractions include service, cleanliness, facilities support and collection activities, (2) characteristics of visitors include visitor origin, sex, age, distance, duration of visit, number of visitors, education, motivation visit (tourist), the type of group (group), and the activity of visiting (see or ride an elephant). The model was used to determine the chances of qualitative factors that influence visitor satisfaction. Optimization parameters used software Minitab 16. The results showed that the significant factors of visitor satisfaction are distances, services, duration of visit and college and that does not include the effect is not real visitor origin, sex, age, number of visitors, motivation visit (tourist), the type of group (group), the activity of visiting (see or ride an elephant) hygiene, supporting facilities and collection activities. For visitor satisfaction improvement strategies by improving the attractiveness of the object ecotourism, ticket services, security, additional variations tourist attractions, and the addition of facilities and supporting infrastructure for the convenience of visitors. Tourist attractions, improvement and addition the facilities and supporting infrastructure for the convenience of visitors. Keywords: elephant conservation center, guest satisfaction